The Impact of Television Advertising and Sales Promotion on Generation Z Consumers’ Purchase Intention for Product X Sachet in the Greater Malang Area - Made Budiramdani Kusuma; Sunardi Sembiring (Jurnal Wacana Ekonomi, 2025)
This study aims to analyze the influence of television advertising and sales promotion on the purchase interest in HiLo Sachet products among Generation Z consumers in the Greater Malang area. The research employs a quantitative approach using a survey method involving 402 respondents selected through purposive sampling. Data were analyzed using multiple linear regression to examine the effect of each variable. The findings indicate that both television advertising and sales promotion have a positive and significant influence on purchase interest, with a simultaneous contribution of 94.4%. These results suggest that an integrated marketing communication strategy, particularly the combination of persuasive advertising messages and attractive sales promotion programs, is highly effective in shaping purchase interest among Generation Z consumers. This study provides managerial implications for strengthening marketing strategies in the FMCG sector, especially in enhancing consumer appeal and driving purchase decisions among young consumers.